Control of Flexibility and Pore Structure of Tetraethylorthosilicate/ Methyltriethoxysilane Aerogels by Hybridization - Kim, Chang-Yeoul; Rum Jang, A. (Asian Journal of Chemistry, 2012)
We found that the flexibility, pore structures such as pore sizes, porosity and specific surface area could be controlled by changing ratio of tetraethylorthosilicate/methyltriethoxysilane (TEOS/ MTEOS). A methyl functional group of MTEOS causes the difficulty of hydrolysis and condensation reactions, so that strong basic catalyst needs to be added for the gellation of MTEOS. Therefore, increasing of MTEOS ratio forms larger pore sizes and large primary particles with ca. 1 μm. MTEOS-based aerogels show the lowest specific area due to macropores with more than 1000 nm, although they are very flexible to elongate two times as long as their original sample length. For TEOS/MTEOS hybrid aerogels with 1:1 molar ratio, they have the largest specific surface area and pore volume, a little flexibility and hydrophobicity due to the remaining alkyl functional groups. This research presents the possibility of controlling flexibility, pore structures, hydrophobicity through hybridization of alkoxide and silane. It suggests a way of overcoming weaknesses of silica aerogels like brittleness and hydrophilicity.